Convection in mineral wool used as insulation for buildings - Stankevičius, Vytautas; Paukštys, Valdas; Bliužius, Raimondas; Šadauskienė, Jolanta; Turskis, Zenonas; Samajauskas, Rolandas (Journal of Civil Engineering and Management, 2013)
The paper considers the velocities of air movement in the ventilated air gaps of walls and focuses on pressure fields in both wall models arranged in a climatic chamber and exploited houses. The article investigates the influence of air movement on heat transfer through walls applying numerical modelling methods and conducting experiments in the climatic chamber. The thermal effects of air flows have been described with reference to the Nusselt number defined as the ratio of average convective and conductive heat fluxes and heat flux through still air.